The Economic Influence of Breastfeeding on the Health Cost of Newborns. (May 2019) - Santacruz-Salas, Esmeralda; Aranda-Reneo, Isaac; Hidalgo-Vega, Álvaro; Blanco-Rodriguez, José M.; Segura-Fragoso, Antonio
Background: Breastfeeding provides health benefits for women and newborns. However, few studies have explored how these health benefits translate into economic savings. Research aim: This study aimed to estimate the healthcare costs savings generated by exclusive breastfeeding for healthy newborns. Methods: We designed a longitudinal two-group observational study that included healthy women and newborns ( N = 236) in Toledo, Spain. Over the first 6-months of the infants' lives, we reviewed their clinical histories to determine their consumption of healthcare resources and the type of nutrition provided. The sample was categorized into two groups: exclusive breastfeeding ( n = 46) and non-exclusive breastfeeding for 6 months ( n = 190). Two-part regression models were applied to determine whether there were differences in healthcare costs between the groups. Results: The average age of the women was 32 ( SD : 5.3). The average birth weight of the newborns was 3.3 kg. ( SD : 0.38). At 6 months, 19.5% ( n = 46) of the women breastfed exclusively, 28.4% ( n = 67) combined breastfeeding with formula, and 45.8% ( n = 108) used formula only. Healthcare costs during follow-up reached €785.58 (44% for specialized care, 42% for primary care, 9.8% for medical emergencies, 3% for medications and approximately 1% for medical tests). The statistical analysis estimated a lower healthcare cost of between €454.40 and €503.50 for exclusively breastfed newborns. Conclusion: Breastfeeding generated savings in healthcare costs; therefore, it could be a cost-efficient option compared with alternatives. Researchers who evaluate the efficiency of strategies that promote breastfeeding can contribute to the sustainability of health services.